Human–Environmental Overlap Of Resistant Enterobacterales: Genomic Evidence Linking Coastal Waters And Community Carriage Of Antimicrobial Resistance In A Low- And Middle-Income Setting - Opintan, J.A.; Egyir, B.; Appiah-Korang, L.; Obeng-Nkrumah, N.; Sarpong, A.; et al. (Frontiers in Antibiotics, 2025)
Background: Coastal waters contaminated by antimicrobial resistant hotspots may serve as reservoirs for third-generation cephalosporin resistant Enterobacterales (3GCR-E), extended-spectrum b-lactamase (ESBL)- producers, and carbapenem-resistant Enterobacterales (CRE), but their role in driving human carriage remains poorly understood. Aim: We investigated intestinal carriage of 3GCR-E, ESBL-producers, and CRE in coastal and inland communities in Accra, Ghana, and examined the genomic overlap between human and wastewater-derived CRE isolates. Methods: A comparative cross-sectional study was conducted from August 2023 to June 2024 with 800 participants (400 from coastal and 400 from inland communities). We cultured fecal samples from participants and water samples from lagoons and shorelines for 3GCR-E, ESBL-producers, and CRE. The CRE isolates from both human and wastewater were whole genome sequenced for comparison. Results: Overall, 53.6% (n=429/800) of participants carried 3GCR-E, with 43.6% being ESBL-producers and 1.5% being CRE, the latter restricted only to coastal residents. In the pooled analysis, inland residence was independently associated with reduced odds of 3GCR-E carriage (aOR 0.64, 95% CI 0.48–0.85; p = 0.001). For coastal participants, not swimming was protective against ESBL carriage (aOR 0.65, 95% CI 0.42–0.95; p = 0.030). All human and wastewater CRE isolates were E. coli and clustered in mixed-source phylogenetic clades (ST10, ST940) with >95% average nucleotide identity and pairwise SNP differences as low as 2–20. Both human and wastewater sources carried the identical carbapenemase gene blaOXA-181 on overlapping plasmid replicons, with 57–80% concordance across IncFIA, IncFIB (AP001918), IncX1, and Col440I. Conclusions: Our findings indicate a shared resistance gene pool between human and environmental sources, characterized by bidirectional CRE exchange but dominated by an environment-to-human transmission pathway. This underscores the urgent need for effective wastewater treatment and improved sanitation practices to reduce human exposure and curb the spread of antibiotic resistance.
Research Article
Keywords: One Health; Carbapenem-Resistant Enterobacterales; Wastewater; Intestinal Carriage; Ghana; Antimicrobioal Resistance (AMR)